PHYSICAL ACTIVITY EDUCATION FOR ADOLESCENTS AT SMP BRAWIJAYA SMART SCHOOL MALANG - Habibie, Intan Yusuf; Wilujeng, Catur Saptaning (Caring: Jurnal Pengabdian Masyarakat, 2024)
Activity restrictions imposed during the Covid 19 pandemic had an impact on health aspects, especially for adolescents. Activities during a pandemic for teenagers tend to be mostly done at home and there are several lifestyle changes. In addition, a significant decrease in the physical activity of children and adolescents occurred during the pandemic, especially among adolescents who were currently studying high school. Changes in limited physical activity, the presence of a sedentary lifestyle and the tendency to overeat during the pandemic have been associated with an increase in the prevalence of overweight and obesity. The tendency that may occur due to staying at home for a long time will increase the behavior of sitting, watching television, playing with gadgets, lying down more often, which causes reduced energy use and has a higher risk of suffering from non-communicable diseases. So a change intervention is needed for adolescent behavior related to physical activity. This is important in order to support adolescent health and reduce the prevalence of overweight and obesity in adolescents. This community service is carried out with webinars on physical activity. The results of this activity obtained an average increase in pre-test to post-test scores of 10.7 points.